Peran Badan Perencanaan Pembangunan Daerah (BAPPEDA) Dalam Perencanaan Pembangunan : (Studi Kasus Pembangunan Di Daerah Kabupaten Mandailing Natal) - Marwah Auliyani; Muhammad Yafiz (CV. ULIL ALBAB CORP, 2022)
This study aims to examine the role and function of the Regional Development Planning Agency (BAPPEDA) in development in Mandailing Natal Regency. The research method used is a qualitative research method. Therefore the researchers used this type of qualitative research. Therefore, the researchers used the interview method, as well as direct observation. Researchers took data sources in the form of primary data and secondary data. Where is meant by primary data, namely data obtained directly, that is, as used by researchers in this study, namely interviews and direct observation. As for what is meant by secondary data, namely data obtained indirectly, namely data obtained from other than sources. The result of this research is that the development in Mandailing Natal Regency is in accordance with the planning of BAPPEDA of Mandailing Natal Regency, but has not been fully implemented.